PEMBEKUAN GURITA (Octopus vulgaris) MENGGUNAKAN METODE CPF (Contact Plate Freezer) DI PT. KURNIA SAMUDERA JAYA HAMPARAN PERAK SUMATERA UTARA - Sumartini, Sumartini; Suryono, Muh; Saputra, Eko Novi; Sulastri, Inong (JURNAL BLUEFIN FISHERIES, 2023)
Octopus is one of the fishery commodities that is very easy to experience quality deterioration and therefore it must be done within a very short time so that the octopus[A1] [D2] remains fresh or does not experience deterioration in quality. Therefore, appropriate handling efforts must be made so that the octopus does not experience a decline in quality. One freezing technique that can be applied to the octopus freezing process is the methodContact Plate Freezing (CPF). The aim of this research is to determine the flow of the octopus freezing process (The common octopus) and know about the octopus freezing process (The common octopus) using a machineContact Plate Freezer (CPF) at PT. Kurnia Samudera Jaya Hamparan Perak, North Sumatra. The method used in this research is a qualitative method. The qualitative method referred to is collecting data sources and data collection techniques which have been carried out through observation, documentation, interviews and literature studies. Flow of the octopus freezing process at PT. Kurnia Samudra Jaya includes: receiving raw materials, washing 1, sorting 1, weighing 1, peeling, soaking in salt water, grinding (tumbling), washing 2, weighing 2, sorting 2, sorting, freezing,glazing, packing and labeling, storage, freezing, andstuffing. The principle of freezing octopus is to use a Contact Plate Freezer (CPF) with a coolant in the form of a refrigerant[A3] [D4]. Usagefreon asrefrigerant This was chosen because it has a low and stable freezing point. The conclusion of this research is the principle of octopus freezing (The common octopus) useContact Plate Freezer is to use Freon as a refrigerant. The use of Freon as a refrigerant was chosen because it has a low and stable freezing point. Benefits of using machinesContact Plat Freezer This is a faster freezing time and easier setup for this machine, while the disadvantage is that the capacity is small and the frozen product has a uniform size and is block shaped.